Allometry and Interspecific Differences in the Facial Cranium of Two Closely Related Macaque Species. (12th May 2011) - Ito, Tsuyoshi; Nishimura, Takeshi; Takai, Masanaru
Abstract : Interpreting evolutionary history of macaque monkeys from fossil evidence is difficult, because their evolutionary fluctuations in body size might have removed or formed important morphological features differently in each lineage. We employed geometric morphometrics to explore allometric trajectories of craniofacial shape in two closely related species, Macaca fascicularis and M. fuscata . These two species exhibit a single shared allometric trajectory in superoinferior deflection of the anterior face, indicating that the differences in this feature can be explained by size variation. In contrast, two parallel trajectories are demonstrated in craniofacial protrusion, indicating that even if they are comparable in size, M. fuscata has a higher and shorter face than M. fascicularis . The degree of facial protrusion is most likely a critical feature for phyletic evaluation in the fascicularis group. Such analyses in various macaques would help to resolve controversies regarding phyletic interpretations of fossil macaques.